A systematic review of 10 years of empirical studies on organic food consumption among Malaysian consumers - Jaafar, Nur Aqilah Amalina; Sulaiman, Norhasmah; Sabran, Mohd Redzwan; Zainal Badari, Shamsul Azahari (Malaysian Consumer and Family Economics Association, 2020)
Organic food in Malaysia remains niche despite the positive growth globally due to its positive attributes towards health, safety, and environmental aspects. Numerous researches have been conducted to understand the factors and barriers involved in the consumption of organic food among Malaysians. However, there are still inconclusive findings to understand the scenario as most of the studies were conducted in certain areas in Malaysia. This paper aims to gather and analyze existing literature on the antecedents of organic food consumption among Malaysian consumers. A systematic literature search was carried out using three established databases which resulted in 15 empirical studies in the review. Guided by the Theory of Planned Behaviour, the findings were categorized into the main constructs of the theory. This review provides a comprehensive summary of 10 years’ worth of studies on push-pull factors driving organic food consumption among Malaysians and a proposed conceptual framework by extending the Theory of Planned Behaviour. This paper ends with several recommendations that could be useful for policymakers, researchers as well as consumers.